2018
DOI: 10.22175/mmb2017.07.0037
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Sarcoplasmic Proteome of Beef Muscles with Differential Color Stability during Postmortem Aging

Abstract: Beef color is a muscle-specific trait, and sarcoplasmic proteome influences muscle-specific variations in beef color stability. Postmortem aging influences the color and sarcoplasmic proteome of beef muscles. Nonetheless, muscle-specific changes in sarcoplasmic proteome of beef muscles with differential color stability during aging have not been characterized yet. Therefore, our objective was to examine the changes in the sarcoplasmic proteome of 3 differentially color stable muscles from beef hindquarters dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 52 publications
6
42
0
Order By: Relevance
“…The MRA values de- (Nair et al, 2018). One possible explanation for this unexpected observation is that the combination of aging and long-term storage of an already color-labile ISM leads to extensive mitochondrial damage and the release of mitochondrial reducing enzymes, which in turn could lead to the observed increase in MRA values.…”
Section: Instrumental Color and Biochemical Attributesmentioning
confidence: 95%
See 4 more Smart Citations
“…The MRA values de- (Nair et al, 2018). One possible explanation for this unexpected observation is that the combination of aging and long-term storage of an already color-labile ISM leads to extensive mitochondrial damage and the release of mitochondrial reducing enzymes, which in turn could lead to the observed increase in MRA values.…”
Section: Instrumental Color and Biochemical Attributesmentioning
confidence: 95%
“…Joseph et al (2012) also reported a greater abundance of β-enolase and creatine kinase in color-stable beef longissimus lumborum steaks than in color-labile psoas major steaks. Moreover, recently, Nair et al (2018) reported that the color-stable longissimus lumborum and semitendinosus steaks had greater abundance of glycolytic enzymes and creatine kinase compared to psoas major steaks during postmortem aging.…”
Section: Sarcoplasmic Proteome Variations Between Ism and Osm Aged Fomentioning
confidence: 99%
See 3 more Smart Citations